Analisis Artemisinin Pada Tanaman Artemisia sacrorum, Ledeb dengan Metode Kromatografi - Purwatiningsih Sugita (Department of Chemistry, 2001)
Artemisinin, a potent antimalarial sesquiterpene endoperoxide. From the leave parts of the medicinal plant Artemisia sacforum, Ledeb were investigated artemisinin by chromatography. The result were compared with standard artemisinin.